Prevalence of chronic obstructive pulmonary disease among TB patients at Royal Prima Hospital - Cristoffel, Abraham; Wienaldi, Wienaldi; Suandy, Suandy (Buletin Kedokteran & Kesehatan Prima, 2024)
Chronic Obstructive Pulmonary Disease (COPD) is a respiratory disease characterized by a reduction in lung capacity and is the third leading cause of death worldwide. COPD is a complex disease involving various environmental and genetic factors. This study aimed to determine the prevalence of COPD among TB patients at Royal Prima Hospital in Medan. This was a retrospective descriptive study with a cross-sectional design. The population of this study was all outpatient TB medical records at Royal Prima Hospital in Medan. Purposive sampling was used, resulting in a sample size of 68 individuals. Data was analyzed univariately using descriptive statistics presented in frequency distribution tables and percentages. The results showed that most COPD patients at Royal Prima Hospital were elderly (73.5%), male (85.3%), employed (64.7%), had a junior high school education (47.1%), had suffered from COPD for less than 10 years (70.3%), and were active smokers (63.2%). Most COPD patients were categorized as having moderate disease (39.7%). It is hoped that Royal Prima Hospital will continue to develop prevention programs for Chronic Obstructive Pulmonary Disease to reduce the number of cases, and that COPD patients who frequently visit healthcare facilities will receive instructions on self-care management for their long-term condition to reduce disease severity.